A copper(i)-catalyzed azide–alkyne click chemistry approach towards multifunctional two-way shape-memory actuators. Issue 22 (18th May 2020) - Liu, Zhong-Cheng; Zuo, Bo; Lu, Hai-Feng; Wang, Meng; Huang, Shuai; Chen, Xu-Man; Lin, Bao-Ping; Yang, Hong
Abstract : Here we report a copper(i )-catalyzed azide–alkyne click chemistry approach towards the fabrication of main chain liquid crystal elastomers. Abstract : Nowadays, two-way shape memory polymeric materials with reversible shape-morphing capability exhibit extraordinary application prospects in robotic, biomedical and intelligent material technologies, and have attracted extensive scientific attention. However, the exploration of facile and efficient preparation protocols for the development of two-way shape memory polymers remains challenging. Here we report a two-step copper-catalyzed azide–alkyne cycloaddition (CuAAC) click chemistry strategy to synthesize a new type of main-chain liquid crystal elastomer (MCLCE) material directly from two small molecule monomers bearing terminal dialkyne and diazide units respectively. The azide–alkyne MCLCEs exhibit highly ordered enantiotropic smectic A phase, fully reversible thermal-actuating behavior and excellent mechanical properties. Furthermore, through doping photothermal dyes, coating electric conductive layers and complex programming protocols, the azide–alkyne MCLCE actuators can be fabricated as multifunctional two-way shape memory actuators, such as photo-responsive actuators, electric-responsive actuators and three-dimensional (3D) shape-morphing actuators, which can perform reversible 1D contraction/expansion, 2D bending/unbending, 3D helical curling/uncurling and diversified shape motion modes. This facile CuAAC in situ polymerization/crosslinking approach might bring a new perspective for the development of two-way shape memory polymeric materials with superior mechanical properties and enhanced shape morphing complexity.